The Cost-Effectiveness of Conventional and Modern Approaches in Wound Care Management in a General Hospital - Ivanda Rian Pratama; Farida Yuliaty (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
Wound care management continues to evolve from traditional techniques toward evidence-based modern practices designed to optimize healing outcomes. This qualitative descriptive study explored the comparative effectiveness and experiential perspectives of conventional and modern wound care methods among healthcare providers and patients in a general hospital in Indonesia. Data were collected through semi-structured interviews, participant observations, and documentation reviews involving participants, including nurses, wound care specialists, and diabetic ulcer patients. Thematic analysis was employed to identify recurring patterns and insights regarding healing progress, patient comfort, and perceived cost-efficiency. The findings revealed four major themes: (1) perceived healing outcomes, where modern methods were viewed as promoting faster tissue regeneration and reduced infection risk; (2) comfort and convenience, as patients receiving modern dressings experienced less pain and fewer dressing changes; (3) professional adaptation and skill demand, highlighting the need for continuous training in modern wound management; and (4) cost and accessibility considerations, where the higher initial cost of modern dressings was offset by shorter healing duration and fewer complications. Overall, participants perceived modern wound care as more effective and patient-centered, although implementation barriers remain regarding resources and staff competence. The study underscores the importance of integrating modern wound care practices into hospital protocols while enhancing professional capacity to ensure sustainable adoption